The Influence of Learning Models and Physics Learning Motivation on Students’ Critical Thinking Skills - Yusuf, Nurfadillah; Ali, M. Sidin; Palloan, Pariabti (Jurnal Pendidikan MIPA, 2025)
This research is an experimental study with a 2×2 factorial design, examining the interaction between learning models and physics learning motivation on students' critical thinking skills, both overall and in terms of high and low levels of learning motivation. In addition, this study also aims to test the interaction between learning models and physics learning motivation on critical thinking skills. The study population consisted of all grade XI students at Madrasah Aliyah Allu Jeneponto in the 2024/2025 Academic Year. The research sample consisted of 64 students, selected through a cluster random sampling technique with a lottery method to determine which classes would serve as the experimental and control groups. To minimize disruption to the ongoing learning process, randomization was conducted at the class level, rather than the individual level. Based on the lottery results, it was determined that class XI.1 was designated as the experimental class, taught using the guided inquiry learning model. In contrast, class XI.3 was designated as the control class, taught using the conventional learning model. Each class consisted of 32 students. Data analysis employed descriptive and inferential statistics, including a two-way ANOVA test with a significance level of 5%. The results showed that the experimental group had an average critical thinking ability 12.81 points higher, with a standard deviation of 2.16, compared to the control group, which had an average of 11.09 points, with a standard deviation of 2.13. Inferential analysis confirmed a significant difference in students' overall critical thinking ability between the two learning models, both in the high-motivation and low-motivation groups. However, no influence was found between the learning model and physics learning motivation on the critical thinking ability of students at Madrasah Aliyah Allu. This shows that the influence of the guided inquiry learning model on critical thinking ability is consistent at all levels of learning motivation. Thus, the application of the guided inquiry learning model has been proven effective in improving students' critical thinking abilities, and learning motivation also plays an important role as an independent factor that supports the improvement of this ability. Keywords: guided inquiry, learning motivation, critical thinking skills.